ASPEK PERDATA TRANSAKSI TERAPEUTIK DALAM HUBUNGAN HUKUM ANTARA DOKTER DENGAN PASIEN - Syarifa Mahila (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
Legal relationship between doctor and patient relationship begins with a vertical pattern that departed from the principles that gave birth father knows best paternalistic relationship. In this connection the position of doctor and patient are not equals. The relationship between doctor and patient gave birth to the legal aspects of the object inspanningsverbintenis perikatannya are best efforts to cure / health maintenance of patients who performed with caution based on knowledge and experience of doctors to seek to cure the patient. When the legal relationship between doctor and patient medical services in an effort to begin from the moment patients who responded to the complaint filed by a doctor. Liability of physician medical services in an effort to include responsibility for ethics, professional responsibility and legal liability. Legal responsibilities relating to the responsibilities of doctors relating to criminal law, civil law and administrative law. In this paper specifically discusses the legal relationship between doctor and patient of aspects of civil law.